Quantifying the effectiveness of ultraviolet-C light at inactivating airborne Mycobacterium abscessus. (February 2023) - Nguyen, T.T.; He, C.; Carter, R.; Ballard, E.L.; Smith, K.; Groth, R.; Jaatinen, E.; Kidd, T.J.; Thomson, R.M.; Tay, G.; Johnson, G.R.; Bell, S.C.; et al.
Summary: Background: Mycobacterium abscessus (MABS) group are environmental organisms that can cause infection in people with cystic fibrosis (CF) and other suppurative lung diseases. There is potential for person-to-person airborne transmission of MABS among people with CF attending the same care centre. Ultraviolet light (band C, UV-C) is used for Mycobacterium tuberculosis control indoors; however, no studies have assessed UV-C for airborne MABS. Aim: To determine whether a range of UV-C doses increased the inactivation of airborne MABS, compared with no-UVC conditions. Methods: MABS was generated by a vibrating mesh nebulizer located within a 400 L rotating drum sampler, and then exposed to an array of 265 nm UV-C light-emitting diodes (LED). A six-stage Andersen Cascade Impactor was used to collect aerosols. Standard microbiological protocols were used for enumerating MABS, and these quantified the effectiveness of UV-C doses (in triplicate). UV-C effectiveness was estimated using the difference between inactivation with and without UV-C. Findings: Sixteen tests were performed, with UV-C doses ranging from 276 to 1104 μW s/cm 2 . Mean (±SD) UV-C effectiveness ranged from 47.1% (±13.4) to 83.6% (±3.3). UV-C led to significantly greater inactivation of MABS (all P -values ≤0.045) than natural decay at all doses assessed. Using an indoor model of the hospital environment, it was estimated that UV-C doses in the range studied here could be safely delivered in clinical settings where patients and staff are present. Conclusion: This study provides empirical in-vitro evidence that nebulized MABS are susceptible to UV-C inactivation.